2019
DOI: 10.1016/j.apsusc.2019.05.307
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostatic dipolar energy of large periodic Ni fcc nanowires, slabs and spheres

Abstract: The computational effort to calculate the magnetostatic dipolar energy, MDE, of a periodic cell of N magnetic moments is an O(N 2) task. Compared with the calculation of the Exchange and Zeeman energy terms, this is the most computationally expensive part of the atomistic simulations of the magnetic properties of large periodic magnetic systems. Two strategies to reduce the computational effort have been studied: An analysis of the traditional Ewald method to calculate the MDE of periodic systems and parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…An implementation of the traditional Ewald method that uses the symmetries of the periodic magnetic system to reduce substantially the computation time have been used in the present research. Details of this implementation and its application to any type of lattice, and especially to nanowire arrays, can be found elsewhere [48].…”
Section: Methodology: Calculation Of the Magnetostatic Dipolar Energymentioning
confidence: 99%
See 1 more Smart Citation
“…An implementation of the traditional Ewald method that uses the symmetries of the periodic magnetic system to reduce substantially the computation time have been used in the present research. Details of this implementation and its application to any type of lattice, and especially to nanowire arrays, can be found elsewhere [48].…”
Section: Methodology: Calculation Of the Magnetostatic Dipolar Energymentioning
confidence: 99%
“…The convergence of the MDAEs and MDEs as a function of the real and reciprocal space cutoffs, r c and g c , respectively, was studied on a previous publication. It was found that the MDAE converges faster than the MDEs and that to obtain the mentioned precision of 10 −6 eV/cell for nanowire arrays, r c should be 38a and g c should be at least 9/a radian/Å, where a is the lattice parameter of bulk Ni or Co [48].…”
Section: Magnetostatic Dipolar Anisotropy Energy and Anisotropy Constmentioning
confidence: 99%